INFLUENCE OF BOTTOMHOLE ZONE TREATMENTS ON THE DURATION OF WATERED GAS WELL FLOWING - Kondrat, R. M.; Dremliukh, N. S.; Matiishyn, L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The problems of gas wells operation, in particular, the impact of waterflooding on their productivity, are characterized. The main analytical dependencies for determining the effect of bottomhole zone treatments on the duration of waterflooding of a watered gas well are presented. For the conditions of a hypothetical model well, the influence of the water factor, tubing diameter, and the degree of reduction of the coefficients of filtration resistances of the bottomhole formation zone (BFZ) on the conditions of waterflooding of a watered gas well was studied using analytical dependencies. The studies were carried out at different tubing diameters (0.0503, 0.062, 0.0759 m) and different degrees of reduction of the filtration resistance coefficients of the BFZ by 3 and 6 times. The research results are presented in the form of graphical dependences of the pressure at the wellhead on the water factor for different values of the tubing diameter and the degree of reduction of the coefficients of the filtration resistances of the BFZ. The generalized research results are summarized in the table. The duration of the fountain period of operation of a watered gas well was estimated by the maximum value of the water factor achieved when the pressure at the wellhead decreases to a given value (0.4 MPa), at which the natural fountain of the well stops. According to the research results, there is a clear tendency to increase the water factor and wellhead pressure with an increase in the degree of decrease in the coefficients of filtration resistances of the BFZ and a decrease in the diameter of the tubing. Depending on the degree of reduction of the coefficients of filtration resistances of the BFZ and the value of the internal diameter of the tubing, the duration of the fountain period of well operation increases by 1.09-1.45 times. The results of the studies performed on the example of a model well indicate the technological efficiency of BFZ treatment to extend the flowing period of a watered gas well. Keywords: well, operation, waterflooding, water factor, bottomhole zone, filtration resistance coefficients, fountaining.